Environmental Geology of Urban Areas - Eyles, Nicholas (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1994)
Summary This paper is the first in a series that will appear in future issues of Geoscience Canada. All 39 papers will be published in one volume by the Geological Association of Canada. The text is primarily intended to be a source of readings for senior undergraduate and graduate students. Many of the papers are state-of-the art summaries and will also be essential reading for professional environmental geologists already working in urban areas. The future well-being of urban society is reliant on an informed and proactive citizenry and it is hoped that the lay reader, urban planner, and busi-ness person can also learn something ofthe environmental geological problems associated with urban areas. For this reason, an extensive glossary of commonly used terms is provided. The book will be an aid to the teaching of academic courses and also be of practical use. Above all, we hope it will inform, interestand stimulate the reader.